The Effect of CYP2B6, CYP2D6, and CYP3A4 Alleles on Methadone Binding: A Molecular Docking Study. (9th September 2013) - Kamal, Nik Nur Syazana Bt Nik Mohamed; Lim, Theam Soon; Tye, Gee Jun; Ismail, Rusli; Choong, Yee Siew
Abstract : Current methadone maintenance therapy (MMT) is yet to ensure 100% successful treatment as the optimum dosage has yet to be determined. Overdose leads to death while lower dose causes the opioid withdrawal effect. Single-nucleotide polymorphisms (SNP) in cytochrome P450s (CYPs), the methadone metabolizers, have been showen to be the main factor for the interindividual variability of methadone clinical effects. In this study, we investigated the effect of SNPs in three major methadone metabolizers (CYP2B6, CYP2D6, and CYP3A4) on methadone binding affinity. Results showed that CYP2B6*11, CYP2B6*12, CYP2B6*18, and CYP3A4*12 have significantly higher binding affinity to R -methadone compared to wild type. S -methadone has higher binding affinity in CYP3A4*3, CYP3A4*11, and CYP3A4*12 compared to wild type. R -methadone was shown to be the active form of methadone; thus individuals with CYP alleles that binds better to R -methadone will have higher methadone metabolism rate. Therefore, a higher dosage of methadone is necessary to obtain the opiate effect compared to a normal individual and vice versa. These results provide an initial prediction on methadone metabolism rate for individuals with mutant type CYP which enables prescription of optimum methadone dosage for individuals with CYP alleles.